Cerium oxide particles, their manufacturing process and their use in chemical mechanical polishing

JP2024511723A5Active Publication Date: 2025-02-19RHODIA OPERATIONS SAS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023554067
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-12
Filing Date
2022-03-10
Publication Date
2025-02-19
Estimated Expiration
2042-03-10

AI Technical Summary

Technical Problem

Existing cerium oxide particles for chemical mechanical polishing (CMP) compositions face challenges in achieving high polishing efficiency while maintaining low defectivity, often due to particle size and morphology issues, and the preparation methods are not simple or economical for industrial-scale production.

Method used

Development of cerium oxide particles with a specific roughness index (RI) of at least 5, spheroidal shape, and controlled particle size and surface area, produced through a process involving an aqueous solution of base, nitrate, and organic acid under inert conditions, followed by heat treatment and optional acidification and mechanical deagglomeration.

Benefits of technology

The resulting cerium oxide particles exhibit enhanced polishing efficiency and reduced defectivity, facilitating higher material removal rates with improved process simplicity and cost-effectiveness for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to cerium oxide particles having a roughness index RI of at least 5, a process for their manufacture and their use in chemical mechanical polishing applications. [0010] TIFF2024511723000015.tif20170
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to cerium oxide particles and their use as a component of polishing compositions, particularly chemical mechanical polishing (CMP) compositions. The present invention also relates to a method for preparing the cerium oxide particles.

[0002] More specifically, the present invention provides cerium oxide particles that exhibit good abrasive properties when used in CMP compositions and a method for preparing such particles that is simple, economical and easy to carry out on an industrial scale. [Background technology]

[0003] Ceric oxide is often used in polishing applications. The development of the electronics industry has made it necessary to use ever more compositions for polishing various parts such as disks and dielectric compounds. These compositions, which are usually commercialized in the form of dispersions, must exhibit certain properties. For example, they must be able to remove material to a high degree, which is reflected in their polishing ability. They must also have as low a defectivity as possible; the term "defectivity" is intended to mean, in particular, the amount of scratches that appear on a substrate after it has been treated with the composition. Usually, the dispersions contain particles of submicron dimensions, i.e. generally less than 300 nm, from the standpoint of stability and ease of use. In addition, if the particles present in such dispersions are too fine, their polishing ability decreases, while if the particles are too large, they can contribute to an increase in defectivity.

[0004] Accordingly, several types of cerium oxide particles specifically tailored for CMP applications are known from the prior art.

[0005] WO 2015 / 197656 discloses particles of metal-doped cerium oxide.

[0006] WO 08043703 A1 discloses a suspension of cerium oxide particles in a liquid phase, said particles being secondary particles having an average size of at most 200 nm, said secondary particles comprising primary particles having an average size of at most 100 nm with a standard deviation of at most 30% relative to the value of said average size of the primary particles.

[0007] WO 2015 / 091495 discloses a suspension of cerium oxide particles in a liquid phase, the particles comprising secondary particles including primary particles, the secondary particles having a mean size D50 comprised between 105 and 1000 nm with a standard deviation comprised between 10 and 50% of the value of the mean size of the secondary particles; the primary particles having a mean size D50 comprised between 100 and 300 nm with a standard deviation comprised between 10 and 30% of the value of the mean size of the primary particles.

[0008] The inventors believe that in addition to providing novel cerium oxide particles that exhibit improved performance in CMP, there is still room for improvement in order to obtain a method for preparing such particles that is simple, economical and easy to carry out on an industrial scale. Summary of the Invention

[0009] The applicant has elaborated novel cerium oxide particles that can solve the problems mentioned above.

[0010] One subject of the present invention is therefore cerium oxide particles having a roughness index (RI) of at least 5, in particular in the range from 5 to 20, in particular in the range from 6 to 17. More precisely, the roughness index of a particle is defined by the following formula:

number

[0011] "SSA size" refers to the theoretical average particle size determined from the BET (Brunauer, Emmett and Teller) specific surface area. More specifically, this can be calculated according to the following formula:

number

[0012] To the best of the inventors' knowledge, the roughness index achieved by the particles of the present invention is higher than that of prior art cerium oxide particles, and it is believed that such particles contribute to achieving higher polishing efficiency when used as abrasive particles in CMP compositions or processes.

[0013] The present invention also relates to a process for producing the cerium oxide particles of the present invention, comprising at least the following steps: (a) Under an inert atmosphere, (i) an aqueous solution of a base and (ii) NO3 - , Ce III , optionally Ce IV with (iii) an organic acid or a salt thereof to obtain a mixture, the organic acid being a substituted or unsubstituted C1-C20-alkyl, -alkenyl or -alkynyl carboxylic acid; (b) subjecting the mixture obtained in step (a) to a heat treatment; (c) optionally acidifying the mixture obtained in step (b); (d) optionally washing the solid material obtained at the end of step (b) or (c) with water; (e) optionally subjecting the solid material obtained at the end of step (d) to a mechanical treatment to deagglomerate the particles; The present invention also relates to a process including:

[0014] Advantageously, this process makes it possible to prepare the cerium oxide particles of the invention in a simple manner.

[0015] The present invention also relates to cerium oxide particles obtainable or obtained by the process described above, to a dispersion of the cerium oxide particles of the invention in a liquid medium, to the use of said dispersion or of the particles of the invention for preparing a CMP composition, to a CMP composition comprising said dispersion or said particles, to a polishing process in which said CMP composition is used to remove parts of a substrate and to a semiconductor comprising substrate polished thereby. [Brief description of the drawings]

[0016] [Figure 1] 1 is an image of a particle of the present invention as viewed by transmission electron microscopy. [Diagram 2] 1 is an image of a particle of the present invention as viewed by transmission electron microscopy. [Diagram 3] 1 is an image of a particle of the present invention as viewed by transmission electron microscopy. [Figure 4] 1 is an image of a particle of the present invention as viewed by transmission electron microscopy. [Diagram 5] 1 is an image of prior art cerium oxide particles as viewed by transmission electron microscopy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] These photographs were taken with a JEM-1400 (JEOL) instrument operating at 120 kV.

[0018] In this disclosure, expressions such as "included between" or similar expressions should be understood to include the boundary values.

[0019] The term "cerium oxide" in relation to the particles of the present invention means cerium (IV) oxide, also known as ceric oxide. Cerium oxide generally has a purity of at least 99.8% by weight based on the weight of the oxide. Cerium oxide is generally crystalline ceric oxide. In addition to cerium, some impurities may be present in the oxide. These impurities may come from raw materials or starting materials used in the preparation process of the cerium oxide. The total proportion of impurities is generally less than 0.2% by weight based on the cerium oxide. Residual nitrates are not considered as impurities in this application.

[0020] The term "dispersion" in relation to the cerium oxide particle dispersions of the present invention refers to a system of solid, finely divided cerium oxide particles of submicron size stably dispersed in a liquid medium, said particles optionally containing residual amounts of bound or adsorbed ions, such as, for example, nitrate or ammonium ions.

[0021] The invention will now be explained in more detail according to its different embodiments.

[0022] As explained above, one subject of the present invention is cerium oxide particles having a Roughness Index (RI) of at least 5. More particularly, the Roughness Index of the particles of the present invention may be in the range of 5 to 20, in particular in the range of 6 to 17, and more particularly in the range of 7 to 14.

[0023] The grain roughness index (RI) is defined as:

number

number

[0024] The TEM size is the average effective size of the particles. It is preferably measured on a large number of particles, for example at least 80, preferably at least 90, more preferably at least 100, so that a statistical analysis can be performed. This measurement is usually carried out on one or more photographs of the same sample of cerium oxide particles. The particles are preferably retained so that their image is sufficiently visible in the photograph. According to one embodiment, which will be explained in more detail later, the number of particles having a spheroidal shape preferably represents at least 80.0%, more particularly at least 90.0%, even more particularly at least 95.0% of the particles.

[0025] The specific surface area (SSA) can be determined by adsorption of nitrogen on a powder of cerium oxide particles by the Brunauer-Emmett-Teller method (BET method). This method is disclosed in the standard ASTM D3663-03 (reapproved in 2015). This method is also described in the periodical "The Journal of the American Chemical Society, 60, 309 (1938)". The specific surface area can be measured automatically on a Micromeritics instrument TriStar 3000, following the manufacturer's guidelines. Before the measurement, the samples in powder form shall be degassed by heating in still air at temperatures up to 210 °C in order to remove any adsorbed chemical species.

[0026] Measuring the BET specific surface area makes it possible to calculate the SSA size according to the formula shown above: Given the SSA, this gives the theoretical size of a cerium(IV) oxide particle if it is assumed that the particle is spherical. The TEM size / SSA size ratio is therefore an indicator of the roughness of the particle: the higher this ratio, the coarser the particle. It is believed that cerium oxide particles with a high roughness index can be used in polishing processes such as CMP to improve their efficiency.

[0027] According to a preferred embodiment, the cerium oxide particles of the present invention have a spheroidal shape. To the best of the inventors' knowledge, particles that combine a specific roughness index with a specific spheroidal morphology are conducive to CMP and provide improved results compared to the use of conventional cerium oxide particles (i.e., not spheroidal and not having the required roughness index).

[0028] The sphericity ratio SR of the spheroidal cerium oxide particles of the invention may be between 0.8 and 1.0, more particularly between 0.85 and 1.0, even more particularly between 0.90 and 1.0. SR may preferably be between 0.90 and 1.0 or between 0.95 and 1.0. The circularity of the particles is calculated from the measurements of the particle circumference P and projected area A using the following formula:

number

[0029] An ideal sphere has an SR of 1.0, while a spheroidal particle has an SR less than 1.0.

[0030] Circularity is usually determined by dynamic image analysis (DIA). Examples of devices that can be used to perform DIA are Retsch's CAMSIZER® P4 or Sympatec's QicPic®.

[0031] Circularity can be measured in more detail according to ISO 13322-2 (2006). DIA generally requires the analysis of a statistically significant number of particles (e.g., at least 80).

[0032] According to one embodiment, the average size of the cerium oxide particles of the invention may be 30 nm or more. In many cases, the particle size is 70 nm or more. The average size of the cerium oxide particles of the invention may be 500 nm or less. In many cases, the particle size is 300 nm or less, in particular 150 nm or less. In one aspect, the average size of the cerium oxide particles of the invention may be comprised between 140 and 300 nm, in particular between 145 and 270 nm, more particularly between 150 and 250 nm, even more particularly between 155 and 240 nm. The average size is preferably measured from a TEM image. This measurement is preferably carried out on at least 80 particles.

[0033] According to one embodiment, the specific surface area of ​​the cerium oxide particles of the invention may be comprised between 30 and 100 m2 / g, more particularly between 32 and 80 m2 / g, more particularly between 35 and 70 m2 / g, and even more particularly between 36 and 60 m2 / g. The specific surface area is measured on a powder by nitrogen adsorption according to the Brunauer-Emmett-Teller method (BET method), as previously explained.

[0034] In a particular embodiment, the specific surface area is between 15 and 100 m2 / g, more particularly between 20 and 40 m2 / g.

[0035] In another aspect, the present invention provides a cerium oxide particle, said particle having the formula:

number

number

[0036] In certain embodiments, the roughness index RI in this aspect is less than 5.

[0037] To the best of the inventors' knowledge, the carbon weight ratio of the cerium oxide particles according to this embodiment contributes to the compatibility of the cerium oxide particles with other components of dispersions and polishing compositions commonly used in CMP applications.

[0038] The characterization of the spheroid shape, particle size and specific surface area in this embodiment is as described above.

[0039] According to one embodiment, the carbon weight ratio of the cerium oxide particles of the present invention can be in the range of 0.001% to 5% by weight, in particular in the range of 0.1% to 2.5% by weight. This trace amount of carbon can be a trace of the synthesis method used to prepare the particles, which requires certain organic acids. The elemental carbon dosage can be performed using a carbon and sulfur analyzer, such as a Horiba EMIA 320-V2.

[0040] The present invention also relates to a process for producing the cerium oxide particles of the present invention, comprising at least the following steps: (a) Under an inert atmosphere, (i) an aqueous solution of a base and (ii) NO3 - , Ce III , optionally Ce IV with (iii) an organic acid or a salt thereof to obtain a mixture, the organic acid being a substituted or unsubstituted C1-C20-alkyl, -alkenyl or -alkynyl carboxylic acid; (b) subjecting the mixture obtained in step (a) to a heat treatment; (c) optionally acidifying the mixture obtained in step (b); (d) optionally washing the solid material obtained at the end of step (b) or (c) with water; (e) optionally subjecting the solid material obtained at the end of step (d) to a mechanical treatment to deagglomerate the particles; The present invention also relates to a process including:

[0041] It is advantageous to use salts and ingredients of high purity. The purity of the salt may be at least 99.5% by weight, more particularly at least 99.9% by weight.

[0042] In step (a), an aqueous solution of a base (i) is used. In particular, hydroxide-type products can be used as bases. Mention can be made of hydroxides of alkali metals or alkaline earth metals and aqueous ammonia. Secondary, tertiary or quaternary amines can also be used. The aqueous solution of the base can also be degassed beforehand by bubbling an inert gas through it.

[0043] The amount of base used in step (a), expressed as a molar ratio of base / total Ce, is preferably comprised between 4 and 10, preferably between 5 and 8.

[0044] In step (a), NO3 - , Ce III and optionally Ce IV To prepare the solution, in particular nitrates or cerium can be used. IV In the case of being present in an aqueous solution, Ce IV The molar ratio of Ce / total is preferably comprised between 1 / 500000 and 1 / 4000. This molar ratio may in particular be between 1 / 6000 and 1 / 4000. IV / Ce total molar ratio can be used.

[0045] In this preparation method, an aqueous solution of ceric nitrate obtained by reacting nitric acid with ceric oxide hydrate can be used. Ceric oxide is produced by the reaction of Ce in the presence of hydrogen peroxide. III The cation is Ce IV It is conventionally prepared by reacting a cerous salt solution with aqueous ammonia so as to convert it into a cation. It is also particularly advantageous to use a ceric nitrate solution obtained according to the method disclosed in French patent FR 2 570 087 for electrochemical oxidation of a cerous nitrate solution. The ceric nitrate solution obtained according to the teachings of French patent FR 2 570 087 may exhibit an acidity of about 0.6N.

[0046] In step (a), Ce IV If Ce exists, IV can be provided by a salt, which can be cerium (IV) nitrate or ammonium cerium nitrate.

[0047] The amount of nitrate ions in the aqueous solution used in step (a) is NO3 - / Ce III When expressed as a molar ratio, it generally lies between 1 / 3 and 5 / 1. The acidity of the aqueous solution used in step (a) is preferably comprised between 0.8N and 12.0N.

[0048] In step (a), a specific organic acid (iii) is used which is a substituted or unsubstituted C1-C20 alkyl, -alkenyl or -alkynyl carboxylic acid or a salt thereof. The chain length of the alkyl, alkenyl or alkynyl group may be, more particularly, C1-C12, C1-C6 or even C1-C3. The organic acid is preferably an alkyl or alkenyl carboxylic acid, more preferably an alkyl carboxylic acid.

[0049] According to one embodiment, the organic acid is substituted. Examples of substituents include halogen, lower alkyl (i.e. alkyl groups having less than 6 carbon atoms), aryl, alkoxy, hydroxyl, amino, alkylamino, arylamino, alkylsulfinyl, alkylsulfonyl, arylsulfinyl and arylsulfonyl. Preferred substituents are lower alkyl groups, more particularly C1-C3 alkyl groups, in particular methyl groups. In this alkyl, alkenyl or alkynyl group, one or more substituents may be present, in particular one or more C1-C3 alkyl groups, especially one or more methyl groups. Preferably, the organic acid is a C1-C6 alkyl carboxylic acid substituted with at least one C1-C3 alkyl group, more preferably a C1-C3 alkyl carboxylic acid substituted with at least one C1-C2 alkyl group, more preferably a C1-C3 alkyl carboxylic acid substituted with at least one methyl group, even more preferably pivalic acid.

[0050] According to another alternative embodiment, the organic acid is unsubstitued. In this case, the organic acid is preferably an unsubstituted C1-C20 alkyl carboxylic acid, more preferably an unsubstituted C1-C12 alkyl carboxylic acid, more preferably an unsubstituted C1-C6 alkyl carboxylic acid, more preferably an unsubstituted C1-C3 alkyl carboxylic acid, and even more preferably propionic acid.

[0051] In yet another embodiment, the organic acid is a dicarboxylic acid, such as a C2-C8 dicarboxylic acid, such as malonic acid, succinic acid, preferably adipic acid, which may be substituted or, in particular, unsubstituted, as described herein above.

[0052] Suitable salts of the above organic acids include ammonium salts.

[0053] According to one embodiment, the organic acid is present in the form of an aqueous solution. The concentration of the organic acid in the aqueous solution can be, for example, in the range of 1 to 20% by weight, in particular in the range of 2 to 10% by weight, more particularly in the range of 3 to 7% by weight. According to another embodiment, pure, i.e. undiluted, organic acid is used.

[0054] The components (i), (ii) and (iii) contacted to form the mixture in step (a) can be contacted in any order. According to one embodiment, in particular, an aqueous solution of a base (i) and an organic acid (iii) are contacted with each other and the resulting mixture is contacted with an aqueous solution (ii) containing cerium nitrate. In this case, pure (i.e. undiluted) organic acid (iii) can be used, since the solution of the base (i) is already in the form of an aqueous solution. The contacting of the mixture of (i) and (iii) with (ii) can preferably consist of adding (ii) to said mixture while stirring and / or bubbling an inert gas.

[0055] According to an alternative embodiment, an aqueous solution (ii) containing cerium nitrate and an aqueous solution (i) of a base are contacted with each other and the mixture obtained is contacted with an organic acid (iii), which can then be used in the form of its aqueous solution. The contacting of (ii) and (i) can consist of adding (ii) to (i), preferably with stirring and / or with bubbling of an inert gas.

[0056] The organic acid (iii) can be used at a concentration in the range of 1 to 245 mmol / L, in particular in the range of 2 to 150 mmol / L, more particularly in the range of 5 to 100 mmol / L, more particularly in the range of 5 to 50 mmol / L, relative to the total volume of the mixture obtained in step (a). This range is particularly suitable for the formation of well-defined particles.

[0057] The amount of free oxygen in the mixture should be carefully controlled and minimized. For this purpose, one or more of the components (i), (ii) and (iii) used and / or the resulting mixture can be degassed by bubbling an inert gas through it. The term "inert gas" or "inert atmosphere" is intended to mean an atmosphere or gas that does not contain oxygen, which gas can be, for example, nitrogen or argon.

[0058] Step (a) consists of reacting components (i), (ii) and (iii). Step (a) is preferably carried out under an inert atmosphere, in particular in a closed reactor or in a semi-closed reactor with an inert gas sweep. The contacting is generally carried out in a stirred reactor.

[0059] Step (a) is generally carried out at a temperature comprised between 5° C. and 50° C. This temperature may be between 20 and 25° C.

[0060] Step (b) is the thermal treatment of the reaction medium obtained at the end of the preceding step, which may consist of (i) a heating substep and (ii) an ageing substep.

[0061] The heating substep (i) may consist of heating the medium at a temperature generally comprised between 75°C and 95°C, and more particularly between 80°C and 90°C.

[0062] The maturation substep (ii) may consist in maintaining the medium at a temperature comprised between 75°C and 95°C, more particularly between 80°C and 90°C. The duration of the maturation substep (ii) may be comprised between 2 hours and 20 hours. As a rule of thumb, the higher the temperature of the maturation step, the shorter the duration of the maturation substep. For example, if the temperature of the maturation substep is comprised between 85°C and 90°C, for example 88°C, the duration of the maturation substep may be comprised between 2 hours and 15 hours, more particularly between 4 hours and 15 hours. If the temperature of the maturation substep is comprised between 75°C and 85°C, for example 80°C, the duration of the maturation substep may be comprised between 15 hours and 30 hours.

[0063] During step (b), Ce III Ce IV This step can also be carried out under an inert atmosphere, and the comments regarding this atmosphere in step (a) apply here as well. The heat treatment can also be carried out in a stirred reactor.

[0064] In step (c), the mixture obtained at the end of step (b) can be optionally acidified. This step (c) can be carried out by using nitric acid. The reaction mixture can be acidified with HNO3 to a pH below 3.0, more particularly comprised between 1.5 and 2.5.

[0065] In step (d), the solid material obtained at the end of step (b) or step (c) is washed with water, preferably deionized water. This operation makes it possible to reduce the amount of nitrates remaining in the dispersion and to obtain the target conductivity. This step can be carried out by filtering the solid from the mixture and redispersing the solid in water. Filtration and redispersion can be carried out several times if necessary.

[0066] In step (e), a mechanical treatment may be carried out in order to deagglomerate the particles of the solid material obtained at the end of step (d). This step may be carried out by double jet processing or ultrasonic deagglomeration. This step usually results in a sharper particle size distribution and a reduced number of large agglomerated particles. According to one embodiment, the cerium oxide particles have been subjected to a mechanical deagglomeration treatment. According to another embodiment, the cerium oxide particles have not been subjected to a mechanical deagglomeration treatment.

[0067] After step (e), the solid material can be dried to obtain cerium oxide particles in powder form. After step (e), a dispersion of cerium oxide particles in a liquid medium can also be obtained by adding water or a mixture of water and a miscible liquid organic compound.

[0068] A further object of the present invention resides in cerium oxide particles obtainable or obtained by the process described above.

[0069] The present invention also relates to a dispersion of cerium oxide particles in a liquid medium. The dispersion comprises the cerium oxide particles of the present invention and a liquid medium. The liquid medium can be water or a mixture of water and a water-miscible organic liquid. The water-miscible organic liquid must not cause the particles to precipitate or aggregate. The water-miscible organic liquid can be, for example, an alcohol such as isopropyl alcohol, ethanol, 1-propanol, methanol, 1-hexanol; a ketone such as acetone, diacetone alcohol, methyl ethyl ketone; or an ester such as ethyl formate, propyl formate, ethyl acetate, methyl acetate, methyl lactate, butyl lactate, ethyl lactate. The water / organic liquid ratio can be between 80 / 20 and 99 / 1 (wt / wt).

[0070] The proportion of cerium oxide particles in the dispersion may be comprised between 1.0% and 40.0% by weight, expressed as the weight of cerium oxide particles relative to the total weight of the dispersion, and may be comprised between 10.0% and 35.0% by weight.

[0071] The dispersion may also have a conductivity of less than 300 μS / cm, more specifically less than 150 μS / cm, and even more specifically less than 100 μS / cm or 50 μS / cm. The conductivity is measured with a HORIBA, Ltd. conductivity meter 9382-10D.

[0072] The cerium oxide particles of the present invention or the dispersion of the present invention can be used to prepare a polishing composition, more specifically a CMP composition. They are used as a component of a polishing composition, more specifically a CMP composition.

[0073] The present invention also relates to a CMP composition. A CMP composition (i.e., a chemical mechanical polishing composition) is a polishing composition used to selectively remove material from the surface of a substrate. It is used in the field of integrated circuits and other electronic devices. In practice, in the manufacture of integrated circuits and other electronic devices, multiple layers of conductive, semiconductive and dielectric materials are deposited on or removed from a substrate surface. As layers of material are sequentially deposited on or removed from a substrate, the top surface of the substrate may become non-planar and require planarization. Planarization of a surface (i.e., "polishing" a surface) is the process of removing material from the surface of a substrate to form a generally uniform and flat surface. Planarization is useful for removing undesirable surface topography and surface defects, such as rough surfaces, agglomerated materials, crystal lattice defects, scratches and contaminated layers or materials. Planarization is also useful for forming features on a substrate by removing excess deposited material used to fill the features and provide a uniform surface for subsequent metallization and processing.

[0074] The substrate that can be polished with the polishing composition or CMP composition can be, for example, a silicon dioxide based substrate, glass, a semiconductor, or a wafer.

[0075] The particles according to the invention or the dispersion according to the invention can be used for the preparation of a CMP composition.The invention therefore also relates to a CMP composition comprising cerium oxide particles or dispersions such as those defined above.

[0076] The polishing composition or CMP composition typically contains different components other than cerium oxide particles. The polishing composition may include one or more of the following components: abrasive particles other than cerium oxide particles or other than the abrasive particles of the dispersion of the invention; and / or - pH adjusters; and / or surfactants; and / or - rheology modifiers such as viscosity enhancers and coagulants; and / or - an additive selected from non-ionic polymers, cationic polymers, anionic polymers, quaternary ammonium, silanes, sulfonated monomers, phosphonated monomers, acrylates, starches, cyclodextrins and combinations thereof.

[0077] The pH of the polishing composition is generally 1 to 6. Typically, the pH of the polishing composition is 3.0 or higher. Also, the pH of the polishing composition is typically 6.0 or lower.

[0078] The present invention also relates to a method for removing a portion of a substrate comprising polishing the substrate with a polishing composition such as those described above.

[0079] Finally, the invention relates to a semiconductor polished by this method.

[0080] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements in this application to the extent that a term may be unclear, the statements in this application shall control.

[0081] The present invention will be described in more detail in the following examples, but it is not intended that the present invention be limited to these examples. EXAMPLES

[0082] Example 1 A cerium nitrate solution was prepared by mixing 111.3 g of 2.87 M trivalent cerium nitrate, 16.82 g of 68% HNO3, and 3.26 g of deionized water. This solution was charged into a 250 mL semi-closed vessel. Cerium (IV) nitrate was then added to the cerium nitrate solution such that the molar ratio of cerium IV / total cerium was equivalent to 1 / 5000. An aqueous ammonia solution was prepared by mixing 74.55 g of 13.35 M aqueous ammonia and 623.03 g of deionized water. This solution was charged into a jacketed 1 L semi-closed reactor and stirred for 1 hour while bubbling N2 gas at a flow rate of 210 L / h. The above cerium nitrate solution was added to the aqueous ammonia solution over a period of about 30 minutes under the same stirring and N2 bubbling conditions. An organic acid solution was prepared by adding 0.90 g of pivalic acid to 20 g of deionized water, and N2 gas was bubbled through it for 1 hour before being added to the reactor. Under the same stirring conditions, the flow rate of N2 bubbling was reduced (less than 10 L / h) and the temperature of the reaction mixture was raised to 85°C over about 1 hour and maintained for about 4 hours. The reaction mixture was cooled and acidified to pH 2 with 68% HNO3. The supernatant was decanted and the slurry was adjusted to pH 8 with NH4OH.

[0083] The reaction mixture was washed with deionized water by centrifugation, and the washing was repeated until the conductivity of the washing solution was less than 0.04 mS / cm.

[0084] The BET specific surface area determined by nitrogen adsorption was 37.9 m2 / g. The suspension was observed by TEM and the particles were counted and measured for about 80 particles representative of the suspension. The average particle size was 193 nm with a standard deviation of 39 nm, which corresponds to 20% of the average particle size. The SSA size, determined as described herein, was 22 and the roughness index RI, determined as described herein, was 8.8. The carbon fraction was determined to be %C=0.4 wt.%. A TEM photograph of the resulting spheroidal coarse particles is shown in FIG. 1.

[0085] Example 2 A cerium nitrate solution was prepared by mixing 111.3 g of 2.87 M trivalent cerium nitrate, 16.81 g of 68% HNO3, and 3.25 g of deionized water. This solution was charged into a 250 mL semi-closed vessel. Cerium (IV) nitrate was then added to the cerium nitrate solution such that the molar ratio of cerium IV / total cerium was equivalent to 1 / 5000. An aqueous ammonia solution was prepared by mixing 74.20 g of 13.35 M aqueous ammonia, 643.50 g of deionized water, and 0.92 g of pivalic acid. This solution was charged into a jacketed 1 L semi-closed reactor and stirred for 1 h while bubbling N2 gas at a flow rate of 210 L / h. The above cerium nitrate solution was added to the aqueous ammonia solution over a period of about 30 min under the same stirring and N2 bubbling conditions. Under the same stirring conditions, the N2 bubbling flow rate was reduced (<10 L / h) and the temperature of the reaction mixture was raised to 85°C over about 1 h and maintained for about 4 h. The reaction mixture was cooled and acidified to pH 2 with 68% HNO3. The supernatant was decanted and the slurry was brought to pH 8 with NH4OH.

[0086] The reaction mixture was washed with deionized water by centrifugation, and the washing was repeated until the conductivity of the washing solution was less than 0.04 mS / cm.

[0087] The BET specific surface area determined by nitrogen adsorption was 44.8 m2 / g. The suspension was observed by TEM and the particles were counted and measured for about 80 particles representative of the suspension. The average particle size was 165 nm with a standard deviation of 50 nm, which corresponds to 30% of the average particle size. The SSA size, determined as described herein, was 19 and the roughness index RI, determined as described herein, was 8.9. The carbon fraction was determined to be %C=0.37 wt.%. A TEM photograph of the resulting spheroidal coarse particles is shown in FIG. 2.

[0088] Example 3 A cerium nitrate solution was prepared by mixing 222.4 g of 2.87 M trivalent cerium nitrate and 33.9 g of 68% HNO3. This solution was charged into a 250 mL semi-closed vessel. Cerium (IV) nitrate was then added to the cerium nitrate solution such that the molar ratio of cerium IV / total cerium was equivalent to 1 / 5000. An aqueous ammonia solution was prepared by mixing 133.1 g of 15 M aqueous ammonia, 1297.7 g of deionized water, and 0.83 g of pivalic acid. This solution was charged into a jacketed 2 L semi-closed reactor and stirred for 1 h while bubbling N2 gas at a flow rate of 100 L / h. The above cerium nitrate solution was added to the aqueous ammonia solution over a period of about 30 min under the same stirring and N2 bubbling conditions. Under the same stirring conditions, the N2 bubbling flow rate was reduced (<10 L / h) and the temperature of the reaction mixture was raised to 80°C over about 1 h and maintained for about 4 h. The reaction mixture was cooled and acidified to pH 2 with 68% HNO3. The supernatant was decanted and the slurry was brought to pH 8 with NH4OH.

[0089] The reaction mixture was washed with deionized water by centrifugation, and the washing was repeated five times until the conductivity of the washing solution was less than 0.04 mS / cm.

[0090] The BET specific surface area, determined by nitrogen adsorption, was 23 m2 / g. The suspension was observed by TEM and approximately 150 representative particles were counted and measured individually. The average particle size was 81 nm with a standard deviation of 30 nm, which corresponds to 37% of the average particle size. The SSA size, determined as described herein, was 36 and the roughness index RI, determined as described herein, was 2.2. The carbon fraction was determined to be %C=0.21 wt.%. A TEM photograph of the resulting spheroidal coarse particles is shown in FIG. 3.

[0091] Example 4 A cerium nitrate solution was prepared by mixing 222.4 g of 2.87 M trivalent cerium nitrate and 33.9 g of 68% HNO3. This solution was charged into a 250 mL semi-closed vessel. Cerium (IV) nitrate was then added to the cerium nitrate solution such that the molar ratio of cerium IV / total cerium was equivalent to 1 / 5000. An aqueous ammonia solution was prepared by mixing 133.9 g of 14.9 M aqueous ammonia, 1296.8 g of deionized water, and 1.18 g of adipic acid. This solution was charged into a jacketed 2 L semi-closed reactor and stirred for 1 hour while bubbling N2 gas at a flow rate of 100 L / h. The above cerium nitrate solution was added to the aqueous ammonia solution over a period of about 30 minutes under the same stirring and N2 bubbling conditions. Under the same stirring conditions, the N2 bubbling flow rate was reduced (<10 L / h) and the temperature of the reaction mixture was raised to 80°C over about 1 h and maintained for about 4 h. The reaction mixture was cooled and acidified to pH 2 with 68% HNO3. The supernatant was decanted and the slurry was brought to pH 8 with NH4OH.

[0092] The reaction mixture was washed with deionized water by centrifugation, and the washing was repeated five times until the conductivity of the washing solution was less than 0.04 mS / cm.

[0093] The BET specific surface area, determined by nitrogen adsorption, was 35 m2 / g. The suspension was observed by TEM and the particles were counted and measured for about 220 particles representative of the suspension. The average particle size was 87 nm with a standard deviation of 34 nm, which corresponds to 39% of the average particle size. The SSA size, determined as described herein, was 24 and the roughness index RI, determined as described herein, was 3.6. The carbon fraction was determined to be %C=0.61 wt.%. A TEM photograph of the resulting spheroidal coarse particles is shown in FIG. 4.

[0094] Comparative Example 1 A cerium nitrate solution was prepared by mixing 139.1 g of 2.87 M trivalent cerium nitrate, 21.1 g of 68% HNO3, and 4 g of deionized water. This solution was charged into a 250 mL semi-closed vessel. Cerium (IV) nitrate was then added to the cerium nitrate solution such that the molar ratio of cerium IV / total cerium was equivalent to 1 / 5000. An aqueous ammonia solution was prepared by mixing 100.5 g of 13.35 M aqueous ammonia and 795.5 g of deionized water. This solution was charged into a jacketed 1 L semi-closed reactor and stirred for 1 hour while bubbling N2 gas at a flow rate of 210 L / h. The above cerium nitrate solution was added to the aqueous ammonia solution over a period of about 30 minutes under the same stirring and N2 bubbling conditions. Under the same stirring conditions, the N2 bubbling flow rate was reduced (<10 L / h) and the temperature of the reaction mixture was raised to 85°C over about 1 h and maintained for about 4 h. The reaction mixture was cooled and acidified to pH 2 with 68% HNO3. The supernatant was decanted and the slurry was brought to pH 8 with NH4OH.

[0095] The reaction mixture was washed with deionized water by centrifugation, and the washing was repeated until the conductivity of the washing solution was less than 0.04 mS / cm.

[0096] The BET specific surface area, determined from nitrogen adsorption, was 16.8 m2 / g. The suspension was observed under TEM and approximately 150 particles representative of the suspension were individually counted and measured. The average particle size was 87 nm with a standard deviation of 21 nm, which corresponds to 24% of the average particle size. The SSA size, determined as described herein, was 50 and the Roughness Index, RI, determined as described herein, was 1.7. The TEM photograph is shown in FIG. 5.

Claims

1. A process for producing cerium oxide particles comprising the steps of: (a) under an inert atmosphere, (i) an aqueous solution of a base, and (ii) NO 3 - , Ce III , optionally Ce IV contacting an aqueous solution containing the compound (III) with an organic acid or a salt thereof to obtain a mixture, wherein the organic acid is a substituted or unsubstituted C1-C20 alkyl, -alkenyl or -alkynyl carboxylic acid; (b) subjecting the mixture obtained in step (a) to a heat treatment carried out at a temperature ranging from 75° C. to 95° C.; (c) optionally acidifying the mixture obtained in step (b); (d) optionally washing the solid material obtained at the end of step (b) or (c) with water; (e) optionally subjecting the solid material obtained at the end of step (d) to a mechanical treatment to deagglomerate the particles; The process includes:

2. 2. The process according to claim 1, wherein the organic acid is a substituted or unsubstituted C1-C12 alkyl carboxylic acid, preferably an unsubstituted C1-C6 alkyl carboxylic acid or a C1-C6 alkyl carboxylic acid substituted with at least one C1-C3 alkyl group, more preferably a C1-C3 alkyl carboxylic acid substituted with at least one C1-C2 alkyl group, even more preferably a pivalic acid or a dicarboxylic acid.

3. A cerium oxide particle, the particle having a spheroidal shape and having the formula: [0045] (wherein "TEM size" refers to the average size of particles measured from a transmission electron microscope image of at least 80 particles, and "SSA ... [0050] 1. A cerium oxide particle having a roughness index RI defined as: (where SSA represents the BET specific surface area of ​​the particle determined by nitrogen adsorption and ρ represents the theoretical average particle size according to the density of cerium(IV) oxide, which is 7.22 g / cm3) of at least 2, and said particle having a carbon weight ratio in the range of 0.001% to 5% by weight.

4. The cerium oxide particles of claim 3, characterized in that the roughness index RI is at least 3.

5.

5. Cerium oxide particles as described in claim 3 or 4, characterized in that the carbon weight ratio of the particles is in the range of 0.1% by weight to 2.5% by weight.

6. said particles have a circularity SR between 0.8 and 1.0, more particularly between 0.85 and 1.0, even more particularly between 0.90 and 1.0; SR is calculated from the measured values ​​of the perimeter P and area A of the particle projection image by the following formula: [006] It is calculated using Cerium oxide particles according to any one of claims 3 to 5, characterized in that SR is determined by dynamic image analysis (DIA), in particular according to ISO 13322-2 (2006).

7. 7. Cerium oxide particles according to any one of claims 3 to 6, characterized in that the specific surface area of ​​the particles is comprised between 15 and 100 m2 / g, more particularly between 32 and 80 m2 / g, more particularly between 35 and 70 m2 / g and even more particularly between 36 and 60 m2 / g.

8. 8. Cerium oxide particles according to claim 7, characterized in that the specific surface area of ​​the particles is comprised between 20 and 40 m2 / g.

9. 9. Cerium oxide particles according to claim 3, characterized in that the particles have an average size of 30 to 500 nm, in particular 70 to 300 nm, said average size being determined from TEM images.

10. 10. Cerium oxide particles according to claim 9, characterized in that the average size of the particles is comprised between 140 and 300 nm, in particular between 145 and 270 nm, more particularly between 150 and 250 nm, even more particularly between 155 and 240 nm, said average size being determined from TEM images.

11. Cerium oxide particles according to any one of claims 3 to 10, obtainable by a process according to claim 1 or 2.

12. A dispersion of cerium oxide particles according to any one of claims 3 to 10 in a liquid medium.

13. Use of the cerium oxide particles according to any one of claims 3 to 10 or the dispersion according to claim 12 for preparing a polishing composition, more particularly a CMP composition.

14. A polishing composition comprising the cerium oxide particles according to any one of claims 3 to 10 or the dispersion according to claim 12.

15. 15. A method for removing a portion of a substrate, comprising polishing the substrate with the polishing composition of claim 14.